Religious Nationalism and Secularism in Indonesia: A Complex Relationship - Fikri Kamil; Suchada Jirakorn; Nashitah Idris (Artes Libres Institutum, 2025)
Indonesia is a secular state with a deeply religious populace, making the intersection of religious nationalism and secularism a crucial issue in the country’s modern political landscape. This paper investigates how religious groups, particularly Islamic organizations, have influenced public policy and governance in Indonesia, often advocating for a stronger role of religion in state affairs. By exploring the tensions between secular state structures and the rise of religious nationalism, the research sheds light on how religious movements challenge Indonesia’s secular constitution, especially in areas such as education, law, and social policy. The paper contributes to the understanding of how religious nationalism is reshaping Indonesia’s political discourse, examining the implications for democracy, human rights, and national unity. Through an analysis of political debates, policy changes, and religious activism, this paper argues that while religious nationalism has grown in influence, it faces significant challenges in reconciling with Indonesia’s secular ideals. The research offers valuable insights into the complexities of balancing religious expression with democratic values, making a significant contribution to the literature on religious nationalism, secularism, and political theory in Indonesia.